Answer:
Explanation:
assuming your rewriting it in slope-intercept form
-6x + 3y = -18 slope-intercept form is y = mx + b so we must get it in that format
first we divide the 3 from 3y but whatever we do to that we must so to all so -6x and -18 are also going to be divided by 3 and you will get
-2x + y = -6 after dividing everything by 3
now you want to add 2x to the left side to cancel out that -2x but whatever you do to one side you must do to the other so its going to be
y = 2x - 6
This should be your answer hope this helps
y = 2x - 6